Low docosahexaenoic acid status is associated with reduced indices in cortical integrity in the anterior cingulate of healthy male children: A (1)H MRS Study - McNamara, Robert K. (2013)
Docosahexaenoic acid (DHA, 22:6n-3) is the principal omega-3 fatty acid in mammalian brain gray matter, and emerging preclinical evidence suggests that DHA has neurotrophic and neuroprotective properties. This study investigated relationships among DHA status, neurocognitive performance, and cortical metabolism measured with proton magnetic resonance spectroscopy ((1)H MRS) in healthy developing male children (aged 8–10 years, n = 38). Subjects were segregated into low-DHA (n = 19) and high-DHA (n = 19) status groups by a median split of erythrocyte DHA levels. Group differences in (1)H MRS indices of cortical metabolism, including choline (Cho), creatine (Cr), glutamine + glutamate + γ-aminobutyric acid (Glx), myo-inositol (mI), and N-acetyl aspartate (NAA), were determined in the right and left dorsolateral prefrontal cortex (R/L-DLPFC, BA9) and bilateral anterior cingulate cortex (ACC, BA32/33). Group differences in neurocognitive performance were evaluated with the Kaufman Brief Intelligence Test and identical-pairs version of the continuous performance task (CPT-IP). Subjects in the low-DHA group consumed fish less frequently (P = 0.02), had slower reaction times on the CPT-IP (P = 0.007), and exhibited lower mI (P = 0.007), NAA (P = 0.007), Cho (P = 0.009), and Cr (P = 0.01) concentrations in the ACC compared with the high-DHA group. There were no group differences in ACC Glx or any metabolite in the L-DLPFC and R-DLPFC. These data indicate that low-DHA status is associated with reduced indices of metabolic function in the ACC and slower reaction time during sustained attention in developing male children.